2013
DOI: 10.1063/1.4817903
|View full text |Cite
|
Sign up to set email alerts
|

Fermi level influence on the adsorption at semiconductor surfaces—ab initio simulations

Abstract: Chemical adsorption of the species at semiconductor surfaces is analyzed showing the existence of the two contributions to adsorption energy: bond creation and charge transfer. It is shown that the energy of quantum surface states is affected by the electric field at the surface, nevertheless, the potential contribution of electron and nuclei cancels out. The charge transfer contribution is Fermi level independent for pinned surfaces. Thus for Fermi level pinned at the surface, the adsorption energy is indepen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…21 Recently, intensive investigations of ammonia adsorption were conducted by the same authors. 6 They found that ammonia adsorbed on relatively low H-occupied surface decomposes into a NH 2 radical and a H adatom, which is in accordance with the results of Pignedoli et al and Bermudez. 17-20 The adsorption energy is about 2.8 eV for the hydrogen coverage up to 0.75 ML, but for higher coverage the energy is drastically reduced. Therefore, the adsorption is molecular in this region, locating the molecule in the 'on-top' position as the molecular adsorption energy, independent of the coverage, is close to 2.0 eV.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…21 Recently, intensive investigations of ammonia adsorption were conducted by the same authors. 6 They found that ammonia adsorbed on relatively low H-occupied surface decomposes into a NH 2 radical and a H adatom, which is in accordance with the results of Pignedoli et al and Bermudez. 17-20 The adsorption energy is about 2.8 eV for the hydrogen coverage up to 0.75 ML, but for higher coverage the energy is drastically reduced. Therefore, the adsorption is molecular in this region, locating the molecule in the 'on-top' position as the molecular adsorption energy, independent of the coverage, is close to 2.0 eV.…”
Section: Introductionsupporting
confidence: 81%
“…In the recent study we have shown how the adsorption energy depends on the electric charge transfer between solid bulk or the existing surface states and the new states emerging due to the presence of the adsorbate. 5,6 It was shown that in the absence of the charge transfer the adsorption energy attains the value determined by the energy of the bonding. The novel recently introduced idea is the energy dependence on the electronic charge transfer.…”
Section: The Resultsmentioning
confidence: 99%
See 3 more Smart Citations